Implementation of the Problem-Based Learning Model in Islamic Religious Education Learning at Cikal Cendekia Islamic Elementary School - Diana, Ridma; Hariyadi, Hariyadi; Arfrellina, Anggreini; Susanto, Slamet; Arif, Fikriana Kurniati (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2026)
This study aims to describe the implementation of the Problem-Based Learning (PBL) model in Islamic Religious Education learning at Cikal Cendekia Islamic Elementary School. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, with validity ensured through source triangulation. The findings indicate that the implementation of the PBL model enhances student engagement and active participation in the learning process. The stages of implementation include problem orientation, organization of learning activities, independent inquiry, presentation of discussion results, and learning evaluation. Overall, the PBL model proved to be sufficiently effective in improving the quality of learning.